EVALUATION OF EQUITY EDUCATION PROGRAM PACKAGE B ON COMMUNITY LEARNING CENTER (CLC) (Evaluative Study in CLC Cahaya Ilmu Gunung Alam Kabupaten Lebong) - Heri Arianto; Nina Kurniah (UNIB Press, 2019)
This study aims to evaluate the Package B equality education program that seeks to describe: 1). Package B program planning; 2). Implementation of package B program; and 3). Package B program evaluation. This research is evaluative research. The main subjects of the researcher are Managers, Tutors, Residents of the Learning Package B. Data collection is done using the method of interview, observation, and documentation. The technique used in data analysis is data reduction, data display, and data verification. Triangulation is done to explain the validity of data by using sources and methods. The results of this study are 1). The planning of the package B equality education program can be said to be quite good, the implementation of the Package B equality education program is based on the needs of the community, the objective of the Package B equality education program, and clear and good indicators of program achievement. 2). Implementation can be said to have a good learning strategy using various methods and techniques during the learning process. 3). Program evaluation is in accordance with the objectives by seeing the results of students who can apply knowledge in everyday life, and the CLC Cahaya Ilmu institution serves to develop knowledge, skills, attitudes and values.